Effect of plant growth regulators on growth, yield and economics of Indian mustard [Brassica juncea (L.) Czern & Coss] under rainfed condition - Mishra, Anku; Kushwaha, H. S. (Annals of Agricultural Research, 2016)
A field experiment was conducted during winter (rabi) season of 2012-13 and 2013-14 at Chitrakoot,Madhya Pradesh to assess the effect of plant growth regulators on growth, yield and economics ofIndian mustard [Brassica juncea (L.) Czern & Coss]. Plant growth regulators viz. Naphthalene AceticAcid (NAA) @ 50 and 100 ppm at 20 and 40 DAS and Cycocel (CCC) @ 50 and 100 ppm at 45 and 75DAS alone and their combination were applied on mustard crop at various growth stages. Plantgrowth parameters viz. plant height, leaves/plant, dry matter/plant and yield attributes viz. siliquae/plant and 1000-seed weight were significantly enhanced due to application of NAA @ 100 ppm at20 DAS followed by NAA @ 100 ppm at 40 DAS+ CCC @ 100 ppm at 75 DAS. However, root lengthand root spread were conspicuous higher under NAA @ 100 ppm at 40 DAS+ CCC @ 100 ppm at 75DAS. Seed yield was recorded 23.4, 22.1 and 20.4 % greater under NAA @ 100 ppm at 20 DAS, NAA@ 100 ppm at 40 DAS + CCC @ 100 ppm at 75 DAS and NAA @ 50 ppm at 40 DAS than that ofcontrol, respectively. Stover yield was also obtained significantly higher under above treatment.Net returns and benefit: cost ratio was registered significantly more under NAA @ 100 ppm at 20DAS and NAA @ 100 ppm at 40 DAS + CCC @ 100 ppm at 75 DAS.